Pengaruh Leverage, Profitabilitas, Likuiditas, dan Nilai Perusahaan Terhadap Valuasi Perusahaan: The Effect of Leverage, Profitability, Liquidity, and Company Value on Company Valuation - Yuristiawan , Johanna Revania; Nurhikmah, Nurhikmah; Hoerunisa , Ani; Putri, Kaisyah Naila; Rudianto, Rudianto (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
The purpose of this study is to examine how leverage, profitability, and liquidity affect a company's valuation using a quantitative research method through an associative approach. Company valuation is important for assessing performance, prospects, and investor confidence in a company. Meanwhile, leverage is analyzed to determine the extent to which the funding structure affects the company's value, and profitability is used to assess the company's ability to generate sustainable profits. Liquidity is also considered an indicator of the company's ability to meet its short-term obligations. The research results indicate that profitability has the greatest impact on company valuation. Meanwhile, leverage and liquidity have varying effects depending on the financial condition of each business. These results provide benefits for management and investors in developing strategies that can increase company value through capital structure management, operational efficiency, and financial stability.